(untitled) (SCAFFOLD: A SHOWCASE OF VANDERBILT FIRST-YEAR WRITING, 2025)
This essay tries to understand the artistic and religious system of William Blake (1757-1827), a Romantic painter, poet, engraver, and prophet who believed man’s capacity for imagination was God, and published works of unprecedented depth, opacity, and ecstatic visionary instinct. It mainly focuses on how Christ fits into his ideas. For additional context, listen to the author’s reflection on the piece below.